Catalytic cracking reaction method and cracking auxiliary agent

By using ZSM-5 molecular sieve modified with +3 valent phosphorus source, the problem of self-polymerization of phosphorus species in the phosphoric acid or ammonium phosphate modified molecular sieve is solved, the hydrothermal stability and low-carbon olefin selectivity are improved, and catalytic cracking is enhanced Activity and selectivity of the reaction.

CN119220293AActive Publication Date: 2024-12-31CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202310787361.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

During the roasting process, existing ZSM-5 molecular sieve modified with phosphoric acid or ammonium phosphate can easily cause phosphorus species to accumulate, block pores, reduce pore volume and specific surface area, resulting in low activation efficiency of phosphorus aluminum and unable to effectively improve hydrothermal stability and Low carbon olefin selectivity.

Method used

The ZSM-5 molecular sieve modified with +3 valent phosphorus source is adopted to accelerate the migration of phosphorus species into the pore by selecting smaller +3 valent phosphorus sources, which weakens the surface enrichment phenomenon. The coordination effect between phosphorus species and the skeleton aluminum is sufficient, and it is stable and more stable. More skeleton aluminum improves hydrothermal stability.

Benefits of technology

The hydrothermal stability and low-carbon olefin selectivity of phosphorus-modified ZSM-5 molecular sieve are improved, and the activity of catalytic cracking reaction and the selectivity of ethylene and propylene are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220293A_ABST
    Figure CN119220293A_ABST
Patent Text Reader

Abstract

The invention relates to a catalytic cracking reaction method, which is characterized in that hydrocarbon oil is contacted with a mixture of a cracking catalyst and an auxiliary agent under catalytic cracking reaction conditions, and the auxiliary agent takes the dry basis weight of the auxiliary agent as a reference; the phosphorus-modified ZSM-5 molecular sieve is composed of 20-80% by dry basis of a phosphorus-modified ZSM-5 molecular sieve, 1-70% by dry basis of an inorganic binder and 2-60% by dry basis of clay, after the phosphorus-modified ZSM-5 molecular sieve is subjected to hydrothermal aging for 17 h under the conditions of 800 DEG C and 100% water vapor, the electron binding energy of phosphorus in phosphorus species on the surface of the molecular sieve is 135.2 eV, and the crystal retention degree in XRD analysis is 70-110%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a catalytic cracking reaction method and an auxiliary agent used in the method, and more particularly to a catalytic cracking reaction method and a cracking auxiliary agent containing phosphorus-modified ZSM-5 molecular sieve. Background Art

[0002] The cracking reaction of hydrocarbons at high temperature converts long-chain hydrocarbons into high-value-added low-carbon olefins such as ethylene and propylene. ZSM-5 molecular sieve is a medium-pore molecular sieve with high silicon three-dimensional straight channels and MFI structure developed by Mobil Oil Company of the United States (USP3702886). Its unique pore structure gives it good shape-selective catalytic and isomerization performance. ZSM-5 molecular sieve also has the characteristics of high thermal and hydrothermal stability, high specific surface area, wide range of silicon-aluminum ratio, unique surface acidity and low carbon deposition. ZSM-5 molecular sieve is widely used as a catalyst and catalyst carrier, and has been successfully used in production processes such as alkylation, isomerization, disproportionation, catalytic cracking, methanol to gasoline, and methanol to olefins.

[0003] Since 1983, ZSM-5 molecular sieve has been used in catalytic cracking process as a catalytic cracking octane number aid, aiming to improve the octane number of catalytic cracking gasoline and the selectivity of light olefins. In the technology first reported in US3758403, ZSM-5 was used as an active component to increase the production of propylene, and was prepared into FCC catalyst together with REY. US5997728 discloses a technology of using ZSM-5 molecular sieve as an aid to increase the production of propylene, and the molecular sieve is not modified in any way. The propylene yield in the above two technologies is not high. Although HZSM-5 molecular sieve has good shape selectivity and isomerization performance, its disadvantage is poor hydrothermal stability and easy deactivation under harsh high-temperature hydrothermal conditions, which reduces the catalytic performance.

[0004] Mobil Corporation has found that phosphorus can improve the hydrothermal stability of ZSM-5 molecular sieves. At the same time, phosphorus modification of ZSM-5 molecular sieves can selectively convert primary cracking products (such as gasoline olefins) into C3 and C4 olefins, thereby increasing the yield of low-carbon olefins. ZSM-5 molecular sieves can be modified by introducing an appropriate amount of inorganic phosphorus compounds after synthesis to stabilize the framework aluminum under harsh hydrothermal conditions.

[0005] CN1211469A discloses a five-membered ring molecular sieve composition for producing more propylene and ethylene, which is composed of 85-95% by weight of a five-membered ring molecular sieve, 2-10% by weight of phosphorus calculated as oxide, 0.3-5% by weight of alkaline earth metal calculated as oxide, and 0.3-5% by weight of transition metal element calculated as oxide. The composition is used for catalytic thermal cracking reaction to obtain a higher ethylene yield.

[0006] US5171921 discloses a phosphorus-modified ZSM-5 molecular sieve having a silicon-aluminum ratio of 20-60. When HZSM-5 molecular sieve is impregnated with a phosphorus-containing compound and treated with 500-700°C steam, it has a higher activity than HZSM-5 without phosphorus treatment when used for the reaction of converting C3-C20 hydrocarbons into C2-C5 olefins.

[0007] CN102166533A discloses a method for preparing a phosphorus-modified ZSM-5 molecular sieve, which comprises adding the molecular sieve to a phosphorus-containing aqueous solution, reacting for a period of time at a certain pH value, temperature and pressure, and then filtering, drying and calcining to obtain the phosphorus-modified molecular sieve. Thereafter, the phosphorus-modified molecular sieve is added to an aqueous solution containing rare earth ions, reacting for a period of time at a certain temperature and pressure, and then filtering, washing, drying and calcining to obtain a composite modified molecular sieve. The composite modified molecular sieve is used to prepare a model catalyst having higher hydrothermal stability and micro-activity than the unmodified molecular sieve model catalyst and the molecular sieve model catalyst modified by other methods.

[0008] CN106994364A discloses a method for preparing a phosphorus-modified ZSM-5 molecular sieve, which comprises first mixing one or more phosphorus-containing compounds selected from phosphoric acid, diammonium hydrogen phosphate, ammonium dihydrogen phosphate and ammonium phosphate with a ZSM-5 molecular sieve having a high alkali metal ion content to obtain a mixture having a phosphorus loading of at least 0.1 wt% in terms of P2O5, drying and roasting the mixture, and then performing an ammonium crosslinking step and a water washing step to reduce the alkali metal ion content therein to below 0.10 wt%, and then undergoing drying and hydrothermal aging steps at 400-1000°C and 100% water vapor. The phosphorus-containing ZSM-5 molecular sieve obtained by the preparation method has a high total acid content, excellent cracking conversion rate and propylene selectivity, and also has a high liquefied gas yield.

[0009] Although the use of organic / inorganic phosphorus-containing compounds to modify ZSM-5 molecular sieves can inhibit skeleton dealumination and thus improve hydrothermal stability, and the introduction of phosphorus species also has the effect of regulating the properties of the acid center of the ZSM-5 molecular sieve, thereby improving the cracking conversion rate of long-chain alkanes and the selectivity of light olefins, in the roasting process of the prior art, phosphoric acid or ammonium phosphate will self-polymerize due to dehydration to form large molecular phosphorus species such as polyphosphoric acid, which are easily enriched on the outer surface of the molecular sieve, blocking the pores, reducing the pore volume and specific surface area, resulting in a low phosphorus-aluminum activation efficiency, and the ideal effect of improving hydrothermal stability cannot be achieved after phosphorus modification. Summary of the invention

[0010] The inventors found on the basis of a large number of experiments that the phosphorus-modified ZSM-5 molecular sieve prepared by using a solid phosphorus-containing compound with a phosphorus valence of +3 as a precursor has physical and chemical characteristics different from those of the molecular sieve prepared by the conventional +5-valent phosphorus source aqueous solution impregnation method, and can improve the phosphorus-aluminum stabilization efficiency. The phosphorus-modified ZSM-5 molecular sieve is used as a cracking aid for the active component, and its hydrothermal stability, cracking activity and low-carbon olefin selectivity are all improved. Based on this, the present invention is formed.

[0011] Therefore, one of the objects of the present invention is to provide a catalytic cracking reaction method with the participation of a cracking aid having as an active component a phosphorus-modified ZSM-5 molecular sieve with physicochemical characteristics different from those of conventional phosphorus-containing ZSM-5 molecular sieves and improved phosphorus-aluminum stabilization efficiency of the molecular sieve; a second object is to provide a cracking aid used in the reaction method.

[0012] In order to achieve one of the above-mentioned purposes, the first aspect of the present invention provides a catalytic cracking reaction method, which is to contact hydrocarbon oil with a mixture of a cracking catalyst and an auxiliary agent under catalytic cracking reaction conditions, wherein the auxiliary agent is composed of a phosphorus-modified ZSM-5 molecular sieve, an inorganic binder and clay, and is characterized in that after the phosphorus-modified ZSM-5 molecular sieve is hydrothermally aged for 17 hours at 800°C and 100% water vapor conditions, the electron binding energy of the phosphorus element in the surface phosphorus species of the molecular sieve is 135.2 eV, and the crystal retention in XRD analysis is 70% to 110%.

[0013] In order to achieve the second purpose mentioned above, the second aspect of the present invention provides a cracking aid, which is composed of 20-80% of phosphorus-modified ZSM-5 molecular sieve, 1-70% of inorganic binder and 2-60% of clay on a dry basis, based on the dry basis weight of the catalytic cracking aid. It is characterized in that after hydrothermal aging of the phosphorus-modified ZSM-5 molecular sieve at 800°C and 100% water vapor for 17 hours, the electron binding energy of the phosphorus element in the phosphorus species on the surface of the molecular sieve is 135.2 eV, and the crystal retention in XRD analysis is 70% to 110%.

[0014] The catalytic cracking reaction method provided by the present invention is carried out in the presence of a catalytic cracking aid containing a phosphorus-modified ZSM-5 molecular sieve with special physicochemical parameters; the phosphorus-modified ZSM-5 molecular sieve with special physicochemical parameters is obtained by selecting a +3-valent phosphorus source with relatively small molecules for modification; the +3-valent phosphorus source accelerates the migration process of phosphorus species into the pores of the ZSM-5 molecular sieve, the surface enrichment phenomenon of phosphorus species is weakened, the coordination effect of phosphorus species and framework aluminum is sufficient, and a quantitative phosphorus-containing compound can stabilize more framework aluminum, so that the phosphorus-modified ZSM-5 molecular sieve has excellent hydrothermal stability. After hydrothermal aging at 800°C and 100% water vapor for 17 hours, the electron binding energy of phosphorus elements in the surface phosphorus species is 135.2eV, and the crystal retention degree in XRD analysis is 70%-110%; the phosphorus-modified ZSM-5 molecular sieve is used as a cracking aid of an active component in a catalytic cracking reaction to improve the selectivity of ethylene and propylene. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is the XPS (P2p Scan) spectrum of the phosphorus-modified ZSM-5 molecular sieve sample RYB-1 in the additive. DETAILED DESCRIPTION

[0016] The catalytic cracking reaction method provided in the first aspect of the present invention is to contact hydrocarbon oil with a mixture of a cracking catalyst and an auxiliary agent under catalytic cracking reaction conditions, wherein the auxiliary agent is composed of a phosphorus-modified ZSM-5 molecular sieve, an inorganic binder and clay, and is characterized in that after the phosphorus-modified ZSM-5 molecular sieve is hydrothermally aged for 17 hours at 800°C and 100% water vapor conditions, the electron binding energy of the phosphorus element in the surface phosphorus species of the molecular sieve is 135.2 eV, and the crystal retention in XRD analysis is 70% to 110%.

[0017] Among the additives used in the method of the present invention, the phosphorus-modified ZSM-5 molecular sieve has a phosphorus binding energy of 134.5 eV characterized by XPS after drying at 100-120°C in an air atmosphere during the preparation process; after hydrothermal aging at 800°C and 100% water vapor, the phosphorus binding energy is 135.2 eV. The phosphorus-modified molecular sieve in the prior art has almost no valence state transition, so the binding energy after drying and aging is 134.8-134.9 eV. The phosphorus binding energy characterized by XPS represents its chemical environment and valence state, and can explain the degree of polycondensation and valence state transition of phosphorus species during drying and hydrothermal aging.

[0018] Among the auxiliary agents used in the method of the present invention, the phosphorus-modified ZSM-5 molecular sieve has a higher crystal retention of 70% to 110%, preferably 95% to 110%, after hydrothermal aging at 800°C and 100% water vapor for 17 hours, which also shows that the phosphorus species has a significant coordination effect with the framework aluminum, so that the framework aluminum is fully protected and the molecular sieve has excellent hydrothermal stability.

[0019] In the auxiliary agent used in the method of the present invention, the phosphorus-modified ZSM-5 molecular sieve has a molar ratio of phosphorus to aluminum of 0.01 to 5, preferably 0.1 to 3.

[0020] Among the auxiliary agents used in the method of the present invention, the phosphorus-modified ZSM-5 molecular sieve is obtained by mixing and grinding a solid phosphorus-containing compound precursor with a phosphorus valence state of +3 and a HZSM-5 molecular sieve to obtain a solid phase mixture; the solid phase mixture is subjected to a heating and melting treatment, and the heated and melted solid phase mixture is cooled to room temperature and then subjected to a roasting treatment; or, the HZSM-5 molecular sieve is contacted and impregnated with an aqueous solution of a phosphorus-containing compound with a phosphorus valence state of +3, and then dried and roasted. The phosphorus-containing compound with a phosphorus valence state of +3 can be selected from phosphorous acid and / or ammonium phosphite. The impregnation is carried out at a water-sieve weight ratio of 0.5 to 2 at room temperature for 0.5 to 10 hours; the drying is carried out in an atmosphere of air at 100 to 120°C for 2 to 24 hours; the roasting is carried out in an atmosphere of air at 200 to 800°C for 0.5 to 12 hours. The heating and melting treatment has a temperature higher than the melting point of the solid phosphorus-containing compound and lower than the temperature at which the solid phosphorus-containing compound decomposes or dehydrates, and the treatment time is 2 to 72 hours. The molar ratio of the phosphorus-containing compound precursor with a phosphorus valence state of +3 to the HZSM-5 molecular sieve is (0.1 to 5):1, preferably (0.5 to 2.5):1, wherein the HZSM-5 molecular sieve is calculated as aluminum and the phosphorus-containing compound is calculated as phosphorus. The HZSM-5 molecular sieve is obtained by reducing the sodium content of ZSM-5 molecular sieve to Na2O <0.1wt% through ammonium exchange, and the silicon-aluminum ratio (molar ratio of silicon oxide to aluminum oxide, the same below) ranges ≥10, usually 10 to 200.

[0021] Regarding the phosphorus-modified ZSM-5 molecular sieve in the catalyst of the present application, the present application also introduces the contents of the Chinese invention application with application number 202210899906.6 and application date July 28, 2022 for reference.

[0022] In the method of the present invention, in the mixture of the cracking catalyst and an auxiliary agent, the content of the auxiliary agent is preferably 0.1 to 30% by weight.

[0023] The auxiliary agent is preferably composed of 20-80% of phosphorus-modified ZSM-5 molecular sieves on a dry basis, 1-70% of inorganic binders on a dry basis, and 2-60% of clay on a dry basis. More preferably, the phosphorus-modified ZSM-5 molecular sieves on a dry basis account for 20 to 75% by weight of the auxiliary agent dry basis, and most preferably, the phosphorus-modified ZSM-5 molecular sieves on a dry basis account for 25-70% by weight of the auxiliary agent dry basis. The inorganic binder may include a phosphorus-aluminum inorganic binder and / or other inorganic binders. Preferably, the inorganic binder may include 2-45% by weight of the phosphorus-aluminum inorganic binder on a dry basis and 5-30% by weight of the other inorganic binders on a dry basis.

[0024] The cracking catalyst may be a catalytic cracking catalyst commonly used in the art, and its composition includes a common molecular sieve active component of the cracking catalyst, an inorganic binder, clay, etc. The molecular sieve active component of the cracking catalyst includes a Y-type molecular sieve. The Y-type molecular sieve is selected from at least one of PSRY molecular sieve, PSRY-S molecular sieve, PSRY molecular sieve containing rare earth, PSRY-S molecular sieve containing rare earth, USY molecular sieve, USY molecular sieve containing rare earth, REY molecular sieve, REHY molecular sieve and HY molecular sieve.

[0025] In the present invention, the hydrocarbon oil is selected from one or more of crude oil, naphtha, gasoline, atmospheric residue, vacuum residue, atmospheric wax oil, vacuum wax oil, straight-run wax oil, propane light / heavy deoiling, coker wax oil and coal liquefaction products. The hydrocarbon oil may contain heavy metal impurities such as nickel and vanadium and sulfur and nitrogen impurities, such as the sulfur content in the hydrocarbon oil may be as high as 3.0% by weight, the nitrogen content may be as high as 2.0% by weight, and the content of metal impurities such as vanadium and nickel may be as high as 3000ppm.

[0026] In the present invention, the catalytic cracking reaction conditions may be conventional in the art, preferably including: a reaction temperature of 500 to 800°C, such as 550 to 680°C.

[0027] The second aspect of the present invention provides a cracking aid, which is composed of 20-80% of phosphorus-modified ZSM-5 molecular sieve, 1-70% of inorganic binder and 2-60% of clay on a dry basis, based on the dry basis weight of the catalytic cracking aid. It is characterized in that after hydrothermal aging of the phosphorus-modified ZSM-5 molecular sieve at 800°C and 100% water vapor for 17 hours, the electron binding energy of the phosphorus element in the phosphorus species on the surface of the molecular sieve is 135.2eV, and the crystal retention in XRD analysis is 70% to 110%.

[0028] In the cracking aid, the phosphorus-modified ZSM-5 molecular sieve is obtained by mixing and grinding a solid phosphorus-containing compound precursor with a phosphorus valence state of +3 and an HZSM-5 molecular sieve to obtain a solid phase mixture; the solid phase mixture is subjected to a heating and melting treatment, and the heated and melted solid phase mixture is cooled to room temperature and then subjected to a calcination treatment; or, the phosphorus-modified ZSM-5 molecular sieve is obtained by contacting and impregnating the HZSM-5 molecular sieve with an aqueous solution of a phosphorus-containing compound with a phosphorus valence state of +3, and then drying and calcining.

[0029] The phosphorus-modified ZSM-5 molecular sieve in the cracking aid has a molar ratio of phosphorus to aluminum of 0.01 to 5, preferably 0.1 to 3.

[0030] The inorganic binder in the cracking aid may include a phosphorus-aluminum inorganic binder and / or other inorganic binders. Preferably, the inorganic binder may include 2-45 wt% of the phosphorus-aluminum inorganic binder on a dry basis and 5-30 wt% of the other inorganic binders on a dry basis.

[0031] Based on the dry weight of the phosphorus-aluminum inorganic binder, the phosphorus-aluminum inorganic binder includes 15-40 weight% of aluminum component calculated as Al2O3, 45-80 weight% of phosphorus component calculated as P2O5, and its P / Al weight ratio is 1.0-6.0, the pH value is 1-3.5, and the solid content is 15-60 weight%; for example, it includes 15-40 weight% of aluminum component calculated as Al2O3, 45-80 weight% of phosphorus component calculated as P2O5; preferably it contains 15-35 weight% of aluminum component calculated as Al2O3, 50-75 weight% of phosphorus component calculated as P2O5, and its P / Al weight ratio is preferably 1.2-6.0, more preferably 2.0-5.0, and the pH value is preferably 1.5-3.0. Preferably, the phosphorus-aluminum inorganic binder comprises 20-40 wt% aluminum component in terms of Al2O3 and 60-80 wt% phosphorus component in terms of P2O5, based on the dry weight. The phosphorus-aluminum inorganic binder can be prepared by the following steps: alumina source, clay (e.g., rectorite, kaolin) and water are slurried and dispersed into a slurry with a solid content of 5-50 wt%; wherein the alumina source is aluminum hydroxide and / or aluminum oxide (e.g., pseudo-boehmite, SB powder, γ-alumina) that can be peptized by acid, relative to 15-50 weight parts of the alumina source in terms of Al2O3; concentrated phosphoric acid is added to the slurry at a weight ratio of P / Al=1-6 under stirring, and the resulting mixed slurry is reacted at 50-99°C for 15-90 minutes; wherein P in P / Al is the weight of phosphorus in phosphoric acid in terms of elemental substance, and Al is the weight of aluminum in the alumina source in terms of elemental substance.

[0032] The other inorganic binder is selected from at least one of pseudo-boehmite, aluminum sol, silica-alumina sol and water glass.

[0033] In the cracking aid provided by the present invention, the clay is well known to those skilled in the art, and the clay can be at least one selected from kaolin, metakaolin, diatomaceous earth, sepiolite, attapulgite, montmorillonite and rectorite, preferably kaolin, metakaolin and rectorite. Based on the dry weight of the aid, it contains 2-60% by weight of clay on a dry basis, preferably 5-55% by weight of clay, and more preferably 15-40% by weight of clay.

[0034] In a specific preparation embodiment of the cracking aid provided by the present invention, an inorganic binder (such as pseudo-boehmite, aluminum sol, silica sol, silica-alumina gel or a mixture of two or more thereof) can be mixed with clay (such as kaolin) and water (such as deionized water and / or deionized water) to form a slurry with a solid content of 10 to 50% by weight, and stirred evenly. The slurry pH is adjusted to 1 to 4 with an inorganic acid such as hydrochloric acid, nitric acid, phosphoric acid or sulfuric acid, and the pH value is maintained. After standing and aging at 20 to 80° C. for 0 to 2 hours, such as 0.3 to 2 hours, aluminum sol and / or silica sol are added, stirred for 0.5 to 1.5 hours to form a colloid, and then a phosphorus-modified ZSM-5 molecular sieve is added to form a catalyst slurry. The solid content of the catalyst slurry is, for example, 20 to 45 weight%, and the stirring is continued and then spray-dried to form microspheres. The microspheres are then calcined, for example, at 350-650°C or 400-600°C, preferably 450-550°C, for 0.5-6 hours or 0.5-2 hours, and then washed with ammonium sulfate (wherein the washing temperature can be 40-70°C, ammonium sulfate: microspheres: water = 0.2-0.8:1:5-15 weight ratio) until the sodium oxide content is less than 0.25% by weight, washed with water and filtered, and then dried.

[0035] In another specific preparation embodiment of the auxiliary agent of the present invention, the phosphorus-modified ZSM-5 molecular sieve, the phosphorus-aluminum inorganic binder and other inorganic binders can be mixed, clay is added, slurried, and spray-dried.

[0036] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0037] X-ray diffraction (XRD) spectra were measured on a Rigaku TTR-3 powder X-ray diffractometer. Instrument parameters: copper target (tube voltage 40 kV, tube current 250 mA), scintillation counter, step width 0.02°, scanning rate 0.4 (°) / min. The ZSM-5 molecular sieve synthesized by the method of Example 1 in CN1056818C was used as a standard sample, and its crystallinity was set to 100%. The relative crystallinity is expressed as a percentage of the sum of the peak areas of the five characteristic diffraction peaks at 2θ between 22.5 and 25.0° of the X-ray diffraction spectra of the obtained product and the standard sample.

[0038] X-ray photoelectron spectroscopy (XPS) was used to analyze the molecular sieve surface and examine the migration of phosphorus compounds using the ESCALAB 250 X-ray photoelectron spectrometer from Thermo Fisher-VG. Instrument parameters: The excitation source was monochromatic AlKα X-ray with a power of 150 W, and the charge shift was corrected using the C1s peak (284.8 eV) from contaminated carbon.

[0039] Unless otherwise specified, the instruments and reagents used in the embodiments of the present invention are commonly used by those skilled in the art.

[0040] The properties of some of the raw materials used in the examples are as follows:

[0041] Pseudo-boehmite is an industrial product produced by Shandong Aluminum Company, with a solid content of 60% by weight.

[0042] Alumina sol is an industrial product produced by Sinopec Catalyst Qilu Branch, with an Al2O3 content of 21.5% by weight.

[0043] Silica sol is an industrial product produced by Sinopec Catalyst Qilu Branch, with a SiO2 content of 28.9% by weight and a Na2O content of 8.9%.

[0044] The kaolin is kaolin specially used for catalytic cracking catalyst produced by Suzhou Kaolin Company, with a solid content of 78% by weight.

[0045] The rectorite was produced by Hubei Zhongxiang Mingliu Rectorite Development Co., Ltd., with a quartz sand content of <3.5% by weight, an Al2O3 content of 39.0% by weight, a Na2O content of 0.03% by weight, and a solid content of 77% by weight.

[0046] SB aluminum hydroxide powder, produced by Condex, Germany, has an Al2O3 content of 75% by weight.

[0047] HRY molecular sieve is an industrial product produced by Sinopec Catalyst Changling Branch, with a rare earth content of 10% by weight.

[0048] PSRY molecular sieve is an industrial product produced by Sinopec Catalyst Changling Branch, with a Na2O content of <1.5% by weight, a P2O5 content of 0.8-1.2% by weight, a unit cell constant of <2.456nm, and a crystallinity of ≥64%.

[0049] Unless otherwise specified, the instruments and reagents used in the embodiments of the present invention are commonly used by those skilled in the art.

[0050] Examples 1-6 illustrate the phosphorus-modified ZSM-5 molecular sieve used in the cracking aid of the present invention and its preparation.

[0051] Example 1

[0052] Take 10.8g of solid phosphorous acid and add it to 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30). After grinding and mixing for 0.5h, transfer it to a Teflon-lined stainless steel high-pressure reactor for a melting process with a heating temperature of 100°C and a time of 10h. After the melting process, wait for the sample to naturally cool to room temperature and then take it out; the above sample is calcined at 550°C for 2h to obtain a phosphorus-modified ZSM-5 molecular sieve sample, recorded as RYB-1.

[0053] Example 1-1

[0054] Take 10.8g of solid phosphorous acid and dissolve it in 145g of deionized water at 25°C, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25°C for 0.5h, move it to an oven and dry it at 120°C for 12h, and calcine it at 550°C in an air atmosphere in a muffle furnace for 2h. The obtained phosphorus-modified ZSM-5 molecular sieve comparison sample is recorded as RYB-1s.

[0055] Example 2

[0056] 15.4 g of solid diammonium hydrogen phosphite was added to 100 g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), which was ground and mixed for 0.5 h and then transferred to a Teflon-lined stainless steel high-pressure reactor for a melting process at a heating temperature of 100°C for 10 h. After the melting process, the sample was taken out after naturally cooling to room temperature. The above sample was calcined at 550°C for 2 h to obtain a phosphorus-modified ZSM-5 molecular sieve sample, recorded as RYB-2.

[0057] Comparative Example 1

[0058] Take 17.4g of diammonium hydrogen phosphate and dissolve it in 145g of deionized water at 25°C, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25°C for 0.5h, move it to an oven and dry it at 120°C for 12h, and calcine it at 550°C in an air atmosphere in a muffle furnace for 2h. The obtained phosphorus-modified ZSM-5 molecular sieve comparison sample is recorded as D-1.

[0059] Comparative Example 2

[0060] Take 15.1g of phosphoric acid solution (mass fraction 85wt%) and dissolve it in 145g of deionized water at 25℃, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25℃ for 0.5h, move it to an oven and dry it at 120℃ for 12h, and calcine it at 550℃ in an air atmosphere in a muffle furnace for 2h to obtain a phosphorus-modified ZSM-5 molecular sieve comparison sample, recorded as D-2.

[0061] In Examples 1, 1-1, 2 and Comparative Examples 1 and 2, the phosphorus-aluminum ratio of the phosphorus-containing compound to the molecular sieve was 1.25.

[0062] The XPS (P2p Scan) spectrum of sample RYB-1 is shown in Figure 1 . Figure 1 The peaks 134.5eV and 135.2eV represent the electron binding energy of phosphorus in the surface phosphorus species of sample RYB-1 after drying and calcination, respectively. The XPS (P2pScan) spectra of RYB-1s and RYB-2 have Figure 1 characteristics.

[0063] The XRD relative crystallinity and crystal retention of RYB-1, RYB-1s, RYB-2, D-1 and D-2 before and after hydrothermal aging at 800℃, 100% water vapor and 17h are shown in Table 1.

[0064] Table 1

[0065]

[0066] Example 3

[0067] Take 6.5g of solid phosphorous acid and add it to 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30). After grinding and mixing for 0.5h, transfer it to a Teflon-lined stainless steel high-pressure reactor for a melting process with a heating temperature of 100°C and a time of 10h. After the melting process, wait for the sample to naturally cool to room temperature and then take it out; the above sample is calcined at 550°C for 2h to obtain a phosphorus-modified ZSM-5 molecular sieve sample, recorded as RYB-3.

[0068] Example 3-1

[0069] Take 6.5g of solid phosphorous acid and dissolve it in 145g of deionized water at 25°C, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25°C for 0.5h, move it to an oven and dry it at 120°C for 12h, and calcine it at 550°C in an air atmosphere in a muffle furnace for 2h. The obtained phosphorus-modified ZSM-5 molecular sieve comparison sample is recorded as RYB-3s.

[0070] Example 4

[0071] 9.3 g of solid diammonium hydrogen phosphite was added to 100 g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), which was ground and mixed for 0.5 h and then transferred to a Teflon-lined stainless steel autoclave for a melting process at a heating temperature of 100°C for 10 h. After the melting process, the sample was taken out after naturally cooling to room temperature. The above sample was calcined at 550°C for 2 h to obtain a phosphorus-modified ZSM-5 molecular sieve sample, recorded as RYB-4.

[0072] Comparative Example 3

[0073] Take 10.5g of diammonium hydrogen phosphate and dissolve it in 145g of deionized water at 25°C, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25°C for 0.5h, move it to an oven and dry it at 120°C for 12h, and calcine it at 550°C in an air atmosphere in a muffle furnace for 2h. The obtained phosphorus-modified ZSM-5 molecular sieve comparison sample is recorded as D-3.

[0074] Comparative Example 4

[0075] 9.2 g of phosphoric acid solution (mass fraction 85 wt%) was dissolved in 145 g of deionized water at 25 ° C, stirred for 0.5 h to obtain a phosphorus-containing aqueous solution, 100 g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30) was added, and modified by impregnation method. After impregnation at 25 ° C for 0.5 h, it was moved to an oven for drying at 120 ° C for 12 h, and calcined at 550 ° C in an air atmosphere in a muffle furnace for 2 h. The obtained phosphorus-modified ZSM-5 molecular sieve comparison sample was recorded as D-4.

[0076] In Examples 3, 3-1, 4 and Comparative Examples 3 and 4, the phosphorus-aluminum ratio of the phosphorus-containing compound to the molecular sieve was 0.75.

[0077] The XPS (P2p Scan) spectra of samples RYB-3, RYB-3s, and RYB-4 all have Figure 1 characteristics.

[0078] The XRD relative crystallinity and crystal retention of RYB-3, RYB-3s, RYB-4, D-3 and D-4 before and after hydrothermal aging at 800℃, 100% water vapor and 17h are shown in Table 2.

[0079] Table 2

[0080]

[0081]

[0082] Example 5

[0083] Take 15.0g of solid phosphorous acid and add it to 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30). After grinding and mixing for 0.5h, transfer it to a Teflon-lined stainless steel high-pressure reactor for a melting process with a heating temperature of 100°C and a time of 10h. After the melting process, wait for the sample to naturally cool to room temperature and then take it out; the above sample is calcined at 550°C for 2h to obtain a phosphorus-modified ZSM-5 molecular sieve sample, recorded as RYB-5.

[0084] Example 5-1

[0085] Take 15.0g of solid phosphorous acid and dissolve it in 145g of deionized water at 25°C, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25°C for 0.5h, move it to an oven and dry it at 120°C for 12h, and calcine it at 550°C in an air atmosphere in a muffle furnace for 2h. The obtained phosphorus-modified ZSM-5 molecular sieve comparison sample is recorded as RYB-5s.

[0086] Example 6

[0087] Take 21.7g of solid diammonium hydrogen phosphite and add it to 100g HZSM-5 molecular sieve (nSiO2 / nAl2O3=30). After grinding and mixing for 0.5h, transfer it to a Teflon-lined stainless steel high-pressure reactor for a melting process with a heating temperature of 100°C and a time of 10h. After the melting process, wait for the sample to naturally cool to room temperature and then take it out; the above sample is calcined at 550°C for 2h to obtain a phosphorus-modified ZSM-5 molecular sieve sample, recorded as RYB-6.

[0088] Comparative Example 5

[0089] Take 24.5g of diammonium hydrogen phosphate and dissolve it in 145g of deionized water at 25°C. Stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25°C for 0.5h, move it to an oven and dry it at 120°C for 12h. Calcinate it at 550°C in an air atmosphere in a muffle furnace for 2h to obtain a phosphorus-modified ZSM-5 molecular sieve comparison sample, recorded as D-5.

[0090] Comparative Example 6

[0091] Take 21.4g of phosphoric acid solution (mass fraction 85wt%) and dissolve it in 145g of deionized water at 25℃, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25℃ for 0.5h, move it to an oven and dry it at 120℃ for 12h, and calcine it at 550℃ in an air atmosphere in a muffle furnace for 2h to obtain a phosphorus-modified ZSM-5 molecular sieve comparison sample, recorded as D-6.

[0092] In Examples 5, 5-1, 6 and Comparative Examples 5 and 6, the phosphorus-aluminum ratio of the phosphorus-containing compound to the molecular sieve was 1.75.

[0093] The XPS (P2p Scan) spectra of samples RYB-5, RYB-5s, and RYB-6 all have Figure 1 characteristics.

[0094] The XRD relative crystallinity and crystal retention of RYB-5, RYB-5s, RYB-6, D-5 and D-6 before and after hydrothermal aging at 800℃, 100% water vapor and 17h are shown in Table 3.

[0095] Table 3

[0096]

[0097] Examples 7-26 illustrate the catalytic cracking aids of the present invention.

[0098] The phosphorus-aluminum inorganic binder used in the embodiment is prepared by the following process:

[0099] 1. NJ1: 1.91 kg of pseudo-boehmite (containing 1.19 kg of Al2O3), 0.56 kg of kaolin (0.5 kg on a dry basis) and 3.27 kg of decationized water were slurried for 30 minutes, and 5.37 kg of concentrated phosphoric acid (mass concentration 85%) was added to the slurry under stirring, with the phosphoric acid addition rate being 0.04 kg of phosphoric acid / min / kg of alumina source, and the temperature was raised to 70°C, and then reacted at this temperature for 45 minutes to obtain a phosphorus-aluminum inorganic binder. The material ratio is shown in Table 4, and the sample number is NJ1.

[0100] 2. NJ2: According to the preparation process of NJ1, the material ratio is shown in Table 9, and the sample number is NJ2.

[0101] Table 4

[0102] Aluminium Phosphate Binder Code NJ1 NJ2 Pseudo-boehmite, kg 1.91 <![CDATA[Al2O3,kg]]> 1.19 SB, kg 0.94 <![CDATA[Al2O3,kg]]> 0.70 Cumulative soil, kg 1.28 Dry basis, kg 1.00 Kaolin, kg 0.56 Dry basis, kg 0.50 Phosphoric acid, kg 5.37 5.36 <![CDATA[P2O5,kg]]> 3.31 3.30 Decationized water, kg 3.27 6.71 Total amount, kg 11.11 14.29 Total dry basis, kg 5.00 5.00 Binder solid content, kg / kg 0.45 0.35 P / Al 2.29 3.89 <![CDATA[Al2O3, wt%]]> 23.82 14.00 <![CDATA[P2O5, wt%]]> 66.18 66.00 Clay, weight % 10.00 20.00 pH 2.20 2.37

[0103] Embodiment 7-9

[0104] Take the phosphorus-modified molecular sieve RYB-1, kaolin and pseudo-boehmite of Example 1, add decationized water and beat for 120 minutes to obtain a slurry with a solid content of 30 weight%, add hydrochloric acid to adjust the pH value of the slurry to 3.0, and then continue to beat for 45 minutes, and then add the phosphorus-aluminum inorganic binder NJ1. After stirring for 30 minutes, the obtained slurry is spray-dried to obtain microspheres, and the microspheres are calcined at 500°C for 1 hour to obtain an additive, numbered Zcat1.

[0105] The molecular sieve RYB-1 was replaced by the phosphorus-modified molecular sieves RYB-1s and RYB-2 of Example 1-1 and Example 2, respectively, and the additives numbered Zcat2 and Zcat3 were prepared by the same preparation process as above.

[0106] In the material proportions of Zcat1, Zcat2 and Zcat3, based on dry weight, phosphorus-modified molecular sieve accounts for 65%, kaolin accounts for 20%, phosphorus-aluminum binder NJ1 accounts for 10%, and pseudo-boehmite accounts for 5%.

[0107] Comparative Examples 7 and 8

[0108] The preparation process and material ratio are the same as those of Example 7, except that the phosphorus-modified molecular sieves D-1 and D-2 of Comparative Examples 1 and 2 are used to replace the molecular sieve RYB-1, respectively, to prepare comparative additives, numbered DZCat1 and DZCat2.

[0109] Examples 10-12

[0110] Take the phosphorus-modified molecular sieve RYB-3 and kaolin of Example 3, add decationized water and aluminum sol and beat for 120 minutes to obtain a slurry with a solid content of 30 wt%, add hydrochloric acid to adjust the pH value of the slurry to 3.0, and then continue to beat for 45 minutes, and then add the phosphorus-aluminum inorganic binder NJ2. After stirring for 30 minutes, the obtained slurry is spray-dried to obtain microspheres, and the microspheres are calcined at 500°C for 1 hour to obtain a catalyst, numbered Zcat4.

[0111] The molecular sieve RYB-3 was replaced by the phosphorus-modified molecular sieves RYB-3s and RYB-4 of Example 3-1 and Example 4, respectively, and catalysts numbered Zcat5 and Zcat6 were prepared according to the above preparation process.

[0112] In the material proportions of Zcat4, Zcat5 and Zcat6, based on dry weight, phosphorus-modified ZSM-5 molecular sieve accounts for 55%, kaolin accounts for 30%, phosphorus-aluminum binder NJ2 accounts for 10%, and aluminum sol accounts for 5%.

[0113] Comparative Examples 9 and 10

[0114] The preparation process and material ratio are the same as those of Example 10, except that the phosphorus-modified molecular sieves D-3 and D-4 of Comparative Examples 3 and 4 are used to replace the molecular sieve RYB-3, respectively, to prepare comparative additives, numbered DZcat3 and DZcat4, respectively.

[0115] Examples 13-15

[0116] Take the phosphorus-modified molecular sieve RYB-5 and kaolin of Example 5, add decationized water and aluminum sol and beat for 120 minutes to obtain a slurry with a solid content of 30 wt%, add hydrochloric acid to adjust the pH value of the slurry to 3.0, and then continue to beat for 45 minutes, and then add the phosphorus-aluminum inorganic binder NJ1. After stirring for 30 minutes, the obtained slurry is spray-dried to obtain microspheres, and the microspheres are calcined at 500°C for 1 hour to obtain a catalyst, numbered Zcat7.

[0117] The molecular sieve RYB-5 was replaced by the phosphorus-modified molecular sieves RYB-5s and RYB-6 of Example 5-1 and Example 6, respectively, and the catalysts numbered Zcat8 and Zcat9 were prepared by the same preparation process as above.

[0118] In the material ratio of Zcat7, Zcat8 and Zcat9, based on dry weight, phosphorus-modified ZSM-5 molecular sieve accounts for 60%, kaolin accounts for 20%, phosphorus-aluminum binder NJ1 accounts for 10%, and aluminum sol accounts for 5%.

[0119] Comparative Examples 11 and 12

[0120] The preparation process and material ratio are the same as those of Example 13, except that the phosphorus-modified molecular sieves D-5 and D-6 of Comparative Examples 5 and 6 are used to replace the molecular sieve RYB-5, respectively, to prepare comparative additives, numbered DZcat5 and DZcat6, respectively.

[0121] The following examples illustrate the catalytic cracking method provided by the present invention.

[0122] Examples 16-18

[0123] The additives Zcat1-Zcat3 were aged at 800°C in a 100% water vapor atmosphere for 17 hours.

[0124] The aged additive was mixed with an industrial FCC equilibrium catalyst (an industrial grade MMC equilibrium catalyst with a light oil micro-reaction activity of 63), and the additive accounted for 10% by weight of the mixture. The mixture was loaded into a fixed bed micro-reaction reactor to evaluate the catalytic cracking ability of the additive on light hydrocarbons. The evaluation conditions were a reaction temperature of 650°C, a regeneration temperature of 620°C, and an additive-to-oil ratio of 3.2.

[0125] The properties of the raw oil are shown in Table 5. The reaction results are shown in Table 6.

[0126] Comparative Examples 13 and 14

[0127] Same as Example 27, except that comparative catalysts DZcat1 and DZcat2 were used to replace Zcat1. The reaction results are shown in Table 6.

[0128] Table 5

[0129]

[0130]

[0131] Table 6

[0132]

[0133] Examples 19-21

[0134] The additives Zcat4-Zcat6 were aged for 17 hours at 800°C in a 100% steam atmosphere. The aged additives were mixed with an industrial FCC equilibrium catalyst (an industrial grade MMC equilibrium catalyst with a light oil micro-reaction activity of 63) and loaded into a fixed bed micro-reaction reactor to evaluate the catalytic cracking ability of the additives for light hydrocarbons. The evaluation conditions were a reaction temperature of 650°C, a regeneration temperature of 620°C, and an agent-oil ratio of 3.2. The reaction results are shown in Table 7.

[0135] Comparative Examples 15 and 16

[0136] Same as Example 19, except that comparative catalysts DZcat3 and DZcat4 were used to replace Zcat4. The reaction results are shown in Table 7.

[0137] Table 7

[0138]

[0139] Examples 22-24

[0140] Catalysts Zcat7-Zcat9 were aged for 17 hours at 800°C in a 100% steam atmosphere. The aged additives were mixed with industrial FCC equilibrium catalysts (industrial grade MMC equilibrium catalysts, light oil micro-reaction activity of 63) and loaded into a fixed bed micro-reaction reactor to evaluate the catalytic cracking ability of the additives for light hydrocarbons. The evaluation conditions were reaction temperature of 650°C, regeneration temperature of 620°C, and catalyst-to-oil ratio of 3.2. The reaction results are shown in Table 8.

[0141] Comparative Examples 17 and 18

[0142] Same as Example 35, except that comparative catalysts DZcat5 and DZcat6 were used to replace Zcat7. The reaction results are shown in Table 8.

[0143] Table 8

[0144]

[0145] Examples 25-27

[0146] Catalysts Zcat1-Zcat3 were aged at 800°C in a 100% steam atmosphere for 17 hours. The aged catalysts were mixed with industrial FCC equilibrium catalysts (industrial grade MMC equilibrium catalysts, light oil micro-reaction activity of 63), and the aged catalysts were loaded into a fixed bed micro-reaction reactor to evaluate the catalytic cracking ability of the catalysts on n-tetradecane.

[0147] The evaluation conditions were reaction temperature 500°C, regeneration temperature 600°C, and catalyst-oil ratio 1.28.

[0148] The reaction results are shown in Table 9.

[0149] Comparative Examples 19 and 20

[0150] Same as Example 25, except that comparative catalysts DZcat1 and DZcat2 were used to replace Zcat1. The reaction results are shown in Table 9.

[0151] Table 9

[0152]

[0153]

[0154] From the above reaction results, it can be seen that the catalytic cracking aid prepared by modifying the ZSM-5 molecular sieve with a phosphorus-containing compound having a phosphorus valence state of +3 has an increased hydrocarbon conversion rate, reduced coke, and improved ethylene and propylene yields compared with the catalytic cracking aid prepared by modifying the ZSM-5 molecular sieve with a phosphorus-containing compound having a phosphorus valence state of +5.

Claims

1. A catalytic cracking reaction method, comprising contacting hydrocarbon oil with a mixture of a cracking catalyst and an auxiliary agent under catalytic cracking reaction conditions, wherein the auxiliary agent is composed of a phosphorus-modified ZSM-5 molecular sieve, an inorganic binder and clay, characterized in that: After the phosphorus-modified ZSM-5 molecular sieve is hydrothermally aged for 17 hours at 800° C. and 100% water vapor, the electron binding energy of the phosphorus element in the surface phosphorus species of the molecular sieve is 135.2 eV, and the crystal retention degree in XRD analysis is 70% to 110%.

2. The catalytic cracking reaction method according to claim 1, characterized in that: After the phosphorus-modified ZSM-5 molecular sieve is hydrothermally aged for 17 hours under the conditions of 800° C. and 100% water vapor, the crystal retention rate in XRD analysis is 95% to 110%.

3. The catalytic cracking reaction method according to claim 1, characterized in that: The phosphorus-modified ZSM-5 molecular sieve has a molar ratio of phosphorus to aluminum of 0.01 to 5, preferably 0.1 to 3.

4. The catalytic cracking reaction method according to claim 1, characterized in that: The phosphorus-modified ZSM-5 molecular sieve is obtained by mixing and grinding a solid phosphorus-containing compound precursor with a phosphorus valence state of +3 and a HZSM-5 molecular sieve to obtain a solid phase mixture; heating and melting the solid phase mixture, cooling the heated and melted solid phase mixture to room temperature, and then calcining the mixture; Alternatively, the HZSM-5 molecular sieve is contacted and impregnated with an aqueous solution of a phosphorus-containing compound having a phosphorus valence state of +3, followed by drying and calcining to obtain the obtained product.

5. The catalytic cracking reaction method according to claim 1, characterized in that: The phosphorus-containing compound having a phosphorus valence state of +3 is selected from phosphorous acid and / or ammonium phosphite.

6. The catalytic cracking reaction method according to claim 1, wherein: In the mixture of the cracking catalyst and an auxiliary agent, the content of the auxiliary agent is 0.1 to 30 weight %.

7. The catalytic cracking reaction method according to claim 1 or 6, wherein: The active component of the cracking catalyst includes Y-type molecular sieve.

8. The catalytic cracking reaction method according to claim 7, wherein: The Y-type molecular sieve is at least one of PSRY molecular sieve, PSRY-S molecular sieve, PSRY molecular sieve containing rare earth, PSRY-S molecular sieve containing rare earth, USY molecular sieve, USY molecular sieve containing rare earth, REY molecular sieve, REHY molecular sieve and HY molecular sieve.

9. The catalytic cracking reaction method according to claim 1, characterized in that: The auxiliary agent is composed of 20-80% of phosphorus-modified ZSM-5 molecular sieve on a dry basis, 1-70% of inorganic binder on a dry basis and 2-60% of clay on a dry basis.

10. The catalytic cracking reaction method according to claim 1, characterized in that: The catalytic cracking reaction conditions include: a reaction temperature of 500-800°C.

11. The catalytic cracking reaction method according to claim 1, characterized in that: The hydrocarbon oil is selected from one or more of crude oil, naphtha, gasoline, atmospheric residue, vacuum residue, atmospheric wax oil, vacuum wax oil, straight-run wax oil, propane light / heavy deoiling, coker wax oil and coal liquefaction products.

12. A cracking aid, based on the dry weight of the catalytic cracking aid, comprising 20-80% of phosphorus-modified ZSM-5 molecular sieve on a dry basis, 1-70% of an inorganic binder on a dry basis, and 2-60% of clay on a dry basis, characterized in that: After hydrothermal aging for 17 hours at 800° C. and 100% water vapor, the phosphorus-modified ZSM-5 molecular sieve has an electron binding energy of 135.2 eV in phosphorus species on the molecular sieve surface, and a crystal retention degree of 70% to 110% in XRD analysis.

13. The cleavage aid according to claim 12, characterized in that The phosphorus-modified ZSM-5 molecular sieve has a molar ratio of phosphorus to aluminum of 0.01 to 5, preferably 0.1 to 3.

14. The cleavage aid according to claim 12, characterized in that The phosphorus-modified ZSM-5 molecular sieve is obtained by mixing and grinding a solid phosphorus-containing compound precursor with a phosphorus valence state of +3 and an HZSM-5 molecular sieve to obtain a solid phase mixture; heating and melting the solid phase mixture, cooling the heated and melted solid phase mixture to room temperature, and then calcining it; or, the phosphorus-modified ZSM-5 molecular sieve is obtained by contacting and impregnating the HZSM-5 molecular sieve with an aqueous solution of a phosphorus-containing compound with a phosphorus valence state of +3, and then drying and calcining it.

15. The cleavage aid according to claim 14, characterized in that The solid phosphorus-containing compound having a phosphorus valence state of +3 is selected from phosphorous acid and / or ammonium phosphite.

16. The cleavage aid according to claim 14, characterized in that The impregnation has a water-to-screen weight ratio of 0.5-2 and is carried out at room temperature for 0.5-10 hours; the drying is carried out in an air atmosphere at 100-120°C for 2-24 hours; the calcination is carried out in an air atmosphere at 200-800°C for 0.5-12 hours.

17. The cleavage aid according to claim 14, characterized in that The heating and melting treatment has a temperature higher than the melting point of the solid phosphorus-containing compound precursor and lower than the temperature at which the solid phosphorus-containing compound precursor decomposes or dehydrates, and the treatment time is 2 to 72 hours.

18. The cleavage aid according to claim 14, characterized in that The molar ratio of the HZSM-5 molecular sieve to the phosphorus-containing compound with a phosphorus valence state of +3 is (0.1-2.5):1, preferably (0.5-1.5):1, wherein the HZSM-5 molecular sieve is calculated as aluminum, and the phosphorus-containing compound with a phosphorus valence state of +3 is calculated as phosphorus.

19. The cleavage aid according to claim 12, wherein The inorganic binder comprises a phosphorus-aluminum inorganic binder, and the phosphorus-aluminum inorganic binder accounts for 5-40% by weight based on the dry basis of the auxiliary agent.

20. The cleavage aid according to claim 19, wherein The inorganic binder also contains at least one selected from pseudo-boehmite, aluminum sol, silica-alumina sol and water glass.

21. The cleavage aid according to claim 12, wherein The clay is selected from at least one of kaolin, sepiolite, attapulgite, rectorite, montmorillonite and diatomaceous earth.

Citation Information

Patent Citations

  • Composite modified molecular sieve improving activity and hydrothermal stability and preparation method thereof

    CN102166533A

  • Process for synthesizing ZSM-5 molecular sieve

    CN1056818C

  • Phosphorus modification method of ZSM-5 molecular sieve

    CN106994364A

  • Phosphorus-modified ZSM-5 molecular sieve and preparation method thereof

    CN117504922A

  • Preparation method for penta-basic cyclic molecular sieve composite

    CN1211469A